2009
DOI: 10.3998/ark.5550190.0010.a15
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural properties of 2-([2.2]paracyclophanyl)-2,3-dihydroquinazolines by cyclocondensation of 2-aminoaryl-benzimidamides with 4-formyl[2.2]paracyclophane catalyzed efficiently by iodine

Abstract: Technical iodine was found to catalyze the condensation between 2-aminoarylbenzimidamide derivatives (1a-i) and 4-formyl[2.2]paracyclophane (2) in absolute ethanol under mild conditions to afford 2-([2.2]paracyclophanyl)-4-arylamino-2,3-dihydroquinazoline derivatives (3a-i) in good yields and with high diastereoselectivity. The obtained products were oxidized easily by KMnO 4 to yield the corresponding 2-([2.2]paracyclophanyl)-4-arylaminoquinazoline derivatives (6a-g). The structure of 3b was conformed by X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…By a similar technique, El-Shaieb in 2009 with co-authors [42] presented a method for the synthesis of aminoquinazolines 59 by aminoarylbenzamidine reaction 1'' and 4formyl The same group of scientists in 2009 [43] investigated the reaction of 2-aminoarylbenzimidamides 1'' with isatoic anhydride 60. It was found that as a result of boiling these substrates in absolute ethanol for 2-3 hours, 2-(2-aminophenyl)-4-arylquinazoline derivatives 61 are formed with a yield of 67-79 % (Scheme 46).…”
Section: Preparation Of 4-phenylaminoquinazolinesmentioning
confidence: 99%
“…By a similar technique, El-Shaieb in 2009 with co-authors [42] presented a method for the synthesis of aminoquinazolines 59 by aminoarylbenzamidine reaction 1'' and 4formyl The same group of scientists in 2009 [43] investigated the reaction of 2-aminoarylbenzimidamides 1'' with isatoic anhydride 60. It was found that as a result of boiling these substrates in absolute ethanol for 2-3 hours, 2-(2-aminophenyl)-4-arylquinazoline derivatives 61 are formed with a yield of 67-79 % (Scheme 46).…”
Section: Preparation Of 4-phenylaminoquinazolinesmentioning
confidence: 99%
“…[2][3][4][5] These findings prompted us to design different quinazoline derivatives for further pharmacological tests. [6][7][8] Unfortunately, synthetic methods for the elaboration of this system are not general in scope, and involve multistep, and often lowyielding, reaction sequences. Different one-pot syntheses for quinazoline derivatives have been described, but they require either high temperature or must be affected in a sealed tube at high temperature.…”
mentioning
confidence: 99%